(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2025)
Since the first years of independence, the development of the education system in our country has been elevated to the level of state policy, and great efforts have been made to ensure that our children acquire modern knowledge and professions in conditions that meet world standards, grow up as physically and spiritually mature people, realize their abilities, talents, and intellectual potential, and cultivate feelings of loyalty and selflessness to the motherland in the hearts of our youth.